Indian philosophy
This classic work is a general introduction to Indian philosophy that covers the Vedic and Epic periods, including expositions on the hymns of the Rig Veda, the Upanisads, Jainism, Buddhismand the theism of the Bhagvadgita. Long acknowledged as a classic, this pioneering survey of Indian thought charts a fascinating course through an intricate history. From the Rig Veda to Ramanuja, Radhakrishnan traces the development of Indian philosophy as a single tradition of thought through the ages. The author showcases ancient philosophical texts and relates them to contemporary issues of philosophy and religion. This second edition with a new Introduction by eminent philosopher J.N. Mohanty, highlights the continuing relevance of the work and the philosophic tradition it represents.